The rare phytocoenofond of forest-steppe zone of Ukraine in aspect of the econet forming (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
In context of the econet forming for forest-steppe zone of Ukraine authors justified the segregation of 52 national key territories and 78 regional ones. Their typological analysis has been given. Rare phytocoenofond of national key territories (including 156 associations) and regional ones (including 95 associations) had been determinated. Rare associations had been analyzed by associatiated character of dominated species in communities, authphytosozological value of dominants, botanical-geographical significance, sozological status. Their sozological categorization has been made; data about distribution of rare syntaxa on segregated key territories of the econet and their protection level have been generalized. The comparative sozological analysis of Right bank of Dnipro area and Left bank of one within forest-steppe zone of Ukraine has been realized.
Keywords: forest-steppe zone of Ukraine, econet, key territory, rare association, rare phytocoenofond, synphytosozological analysis.